How Inflation Changes the Pattern of Production Costs? An Investigation of Raw Materials, Labor, and Overhead - Nauril Arzania; Ida Nurhayati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Manufacturing companies face significant challenges in managing production costs amid economic volatility, particularly during inflationary periods. This study investigates how raw material costs, direct labor costs, and factory overhead costs influence the cost of goods manufactured (COGM), with inflation serving as a moderating variable. The research examines 594 manufacturing companies listed on the Indonesia Stock Exchange during 2021-2023, utilizing purposive sampling methodology. Secondary data was collected from annual financial statements and Bank Indonesia's inflation database. The analytical approach employed descriptive statistics, classical assumption tests, multiple linear regression, and moderated regression analysis (MRA). Results demonstrate that raw material costs (t=273.886, p<0.001), direct labor costs (t=26.885, p<0.001), and factory overhead costs (t=96.285, p<0.001) exhibit significant positive effects on COGM. Inflation significantly moderates the relationship between raw material costs and COGM (t=2.531, p=0.012), but does not moderate direct labor costs (t=0.700, p=0.484) or factory overhead costs (t=-1.668, p=0.096) relationships. The model explains 97% of COGM variance, indicating robust explanatory power. These findings provide crucial insights for manufacturing cost management strategies, particularly emphasizing the need for adaptive raw material procurement policies during inflationary periods. The study contributes to contingency theory application in cost accounting and offers practical implications for manufacturing efficiency optimization.